Edukasi Pembuatan Nugget Ikan Sebagai Upaya Pemanfaatan Potensi Perikanan di Desa Mekar Kecamatan Soropia Kabupaten Konawe - Febriana Muchtar; Hartati Bahar (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
The processing of fish products as a source of animal protein needs to be enhanced and developed to optimize the fisheries sector, especially in coastal areas. In addition to giving an added-value to fresh fish, the development of fish processing positively affects the knowledge of the coastal community regarding the importance of fish processing. Fishery products, especially fish, can be processed into various processed products, for example nuggets. Nuggets are processed food products that are popular from children to adults. Nuggets can be made from various raw materials such as chicken, meat and fish. As a source of animal protein, fish nuggets can be used as a processed source of quality animal protein.This community service project was intended to improve the knowledge about fish processing to produce fish nuggets among housewives in Mekar Village Soropia District Konawe Regency in Southeast Sulawesi Province. A workshop was carried out where housewives learned and practiced making fish nuggets. The activity was successfully held where participants showed strong enthusiasm. This project has improved the knowledge of the participants about fish nuggets production process as a form of fishery product diversification. It is expected that this project give added-value to the fishery products through the diversification of processed fish products.